Onopordum illyricum L., a Mediterranean plant, as a source of anti HIV-1 compounds. (2nd November 2018) - Sanna, C.; Rigano, D.; Cortis, P.; Corona, A.; Ballero, M.; Parolin, C.; Del Vecchio, C.; Chianese, G.; Saccon, E.; Formisano, C.; Tramontano, E.; Esposito, F.
Abstract: Currently, many attempts have been made worldwide to isolate compounds from plants that could prevent transmission of HIV and offer new treatments. In this study, the methanolic extract of Onopordum illyricum aerial parts was evaluated for the inhibition of the HIV-1 reverse transcriptase (RT) ribonuclease H (RNase H), an attractive target for the identification of new antiretroviral inhibitors. Using an HIV-1 reverse transcriptase (RT)-associated RNase H inhibition assay, the bio-guided fractionation of the extract led to the isolation of seven compounds (luteolin, apigenin, hispidulin, arctiin, 1, 5-dicaffeoylquinic acid, and two germacranes, 8α-(5-hydroxy)-angeloylsalonitenolide and onopordopicrin). Among them, luteolin was the most effective on RNase H RT-associated function (IC50 of 12.8 μM), followed by 1, 5-dicaffeoylquinic acid and apigenin with IC50 values of 16.9 and 59.6 μM, respectively. Pure compounds were then assayed for their effects also on HIV-1 integrase (IN). 1, 5-Dicaffeoylquinic acid, arctiin, onopordopicrin, and luteolin exhibited the most potent inhibition with IC50 values ranging from 0.50 to 22.5 μM. 1, 5-Dicaffeoylquinic acid was also able to inhibit the early stages of HIV-1 replication in cell-based assays.